2021
DOI: 10.3390/cancers13081879
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlations in Neurofibromatosis Type 1: A Single-Center Cohort Study

Abstract: Neurofibromatosis type 1 (NF1) is a proteiform genetic condition caused by pathogenic variants in NF1 and characterized by a heterogeneous phenotypic presentation. Relevant genotype–phenotype correlations have recently emerged, but only few pertinent studies are available. We retrospectively reviewed clinical, instrumental, and genetic data from a cohort of 583 individuals meeting at least 1 diagnostic National Institutes of Health (NIH) criterion for NF1. Of these, 365 subjects fulfilled ≥2 NIH criteria, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 67 publications
0
24
0
1
Order By: Relevance
“…Kang et al ( 48 ) studied patients with different mutation types and found that patients with truncating/splicing mutations and large deletions tended to present with a more severe phenotype and earlier onset age than those with missense types. Recently, Scala et al ( 49 ) identified that frameshift variants and whole gene deletion were correlated with skeletal abnormalities, whereas neurofibromas were negatively associated with missense variants. Moreover, they found that the presence of structural brain alterations was associated with c.3721C>T variant, whereas Lisch nodules and endocrinological disorders were more common observed in NF-1 patients with c.6855C>A variant.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al ( 48 ) studied patients with different mutation types and found that patients with truncating/splicing mutations and large deletions tended to present with a more severe phenotype and earlier onset age than those with missense types. Recently, Scala et al ( 49 ) identified that frameshift variants and whole gene deletion were correlated with skeletal abnormalities, whereas neurofibromas were negatively associated with missense variants. Moreover, they found that the presence of structural brain alterations was associated with c.3721C>T variant, whereas Lisch nodules and endocrinological disorders were more common observed in NF-1 patients with c.6855C>A variant.…”
Section: Discussionmentioning
confidence: 99%
“…Как правило, у пациентов с протяженными делециями чаще наблюдаются фациальная дисплазия, задержка психоречевого и психомоторного развития, плексиформные нейрофибромы [25].…”
Section: нейрофиброматоз I типаunclassified
“…This process benefits from both NF1 families and NF1-related animal models. In a recent large cohort study with 365 NF1 subjects included, whole-gene deletions and frameshift variants are found correlated with skeletal abnormalities, including scoliosis and sphenoid bone dysplasia ( 88 ). From another 10 unrelated Chinese families who affected NF1 with main complaint of osseous lesions, five novel pathogenic variants including one missense variant and four frameshift variants are detected ( 89 ).…”
Section: Mutations Of Nf1 or Modifier Genes Related To Different Nf1 Phenotypesmentioning
confidence: 99%